Crests, troughs, and plateaus: Using story theory to explore the experiences of adolescents and young people living with HIV in Kampala, Uganda - Derrick Nuwahereza; Allen Nabisere; Imelda Namatovu; Tom Denis Ngabirano; Charles Peter Osingada (PLoS ONE, 2026)
Introduction Adolescents and young people living with HIV experience significant challenges, including unmet psychosocial and self-management needs and limited access to adequate HIV information. Peer support strategies that allow individuals to share their personal experiences and life stories have shown promise in improving their engagement in care and addressing the psychological and social challenges of living with HIV. However, current care approaches do not optimize individual life stories as a foundation for delivering patient-centered and individualized care. Methods This study applied a story path approach, an innovative way of exploring the experiences of adolescents and young people living with HIV. Specifically, it aimed to identify the high points, low points, and turning points in the health journeys of adolescents and young people living with HIV. This descriptive qualitative study was conducted in 2024. Data were collected through face-to-face individual interviews with adolescents and young people living with HIV and analyzed manually. Results Fifteen participants, aged 15–24 years (average age 21.4, SD 2.4), were interviewed. The findings revealed that participants experienced uplifting from social support provided by friends, family, school authorities, and peers. Despite this support, many participants experienced emotional distress, faced challenges with medication adherence, and struggled with suicidal ideation. Counseling was a vital turning point in helping nearly all participants improve their health trajectories. Conclusions Story theory provides a valuable framework for understanding the health experiences of adolescents and young people living with HIV and for delivering care that is tailored to their unique individual narratives. These findings may be useful to nurses, counselors, and peer supporters involved in the care of this population. Future research should explore ways to integrate story theory into adolescent HIV care services to improve health outcomes for adolescents and young people living with HIV.